Meningkatkan Keterampilan Merias Diri Menggunakan Make Up Melalui Model Explicit Instruction Bagi Anak Tunarungu Kelas VIII SMPLB Painan - Novita, Marthila Wahyu; Fatmawati, Fatmawati (Jurnal Penelitian Pendidikan Khusus, 2022)
This research motivated by problems in class VIII of the Deaf at SMPLB Painan in the skills to plant celery due to the lack of skills in applying make-up. The purpose of the research is to describe the learning process through the explicit instruction method, and to find out whether the explicit instruction method can improve skills of applying make-up.The results showed that the process of learning skills using the explicit instruction method was carried out in two cycles. Cycle I with four meetings. Each cycle begins with planning, implementation observation, analysis and reflection.The results of self-makeup skills using make-up using the explicit instruction method showed increase. This seen from the data before the action of the child's ability to do 12 STEPS, namely: RK 37% and MD 35%. Meanwhile, at the end of the first cycle, RK's ability increased by 37%, 45%, 50%, 58% and MD 35%, 41%, 45%, 54%. In the second cycle, RK's ability increased to 65%, 75%, 87%, 91% and MD 62%, 75%, 83%, 87%.